Cyclodextrin production by cyclodextrin glycosyltransferase from Bacillus circulans DF 9R - Szerman, Natalia; Schroh, Ignacio; Rossi, Ana Lía; Rosso, Adriana Mabel; Krymkiewicz, Norberto; Ferrarotti, Susana Alicia (Elsevier, 2019)
Cyclodextrins (CD) are cyclic oligosaccharides with multiple applications in the food, pharmaceutical, cosmetic, agricultural and chemical industries. In this work, the conditions used to produce CD with cyclodextrin glycosyltransferase from Bacillus circulans DF 9R were optimized using experimental designs. The developed method allowed the partial purification and concentration of the enzyme from the cultural broth and, subsequently, the CD production, using the same cassava starch as enzyme adsorbent and as substrate. Heat-treatment of raw starch at 70 C for 15 min in the presence of adsorbed cyclodextrin glycosyltransferase allowed the starch liquefaction without enzyme inactivation. The optimum conditions for CD production were: 5% (w/v) cassava starch, 15 U of enzyme per gram of substrate, reaction temperature of 56 C and pH 6.4. After 4 h, the proportion of starch converted to CD reached 66% (w/w) and the weight ratio of a-CD:b-CD:c-CD was 1.00:0.70:0.16.